Electron tailoring of thermal and magnetocaloric properties in Tb55TM17.5Al27.5 (TM = Fe, Co, and Ni) metallic glasses - F. Jin; C.M. Pang; S.Y. Li; H.B.C. Yin; W. Li; L.Y. Li; J.Z. Ma; L. Li; J.T. Huo; C.R. Cao; C.C. Yuan (Journal of Materials Research and Technology)
Transition metal (TM) elements play a key role in determining properties of magnetocaloric materials. However, the effect of TM elements on the thermodynamic behavior and magnetocaloric effect (MCE) of metallic glasses (MGs) remains elusive. In this work, ternary Tb55TM17.5Al27.5 (TM = Fe, Co, and Ni) MGs without the complexities induced by high-entropy effects were designed. It is found that both the glass transition temperature (Tg) and the initial crystallization temperature (Tx) significantly increase with decreasing 3d electron number. It leads to the low values of Trg, γ, and γm for Tb55Fe17.5Al27.5, which is consistent with its poor glass forming ability (GFA) as evidenced by the obvious lattice fringes and structural order. Despite the mediocre value of magnetic entropy change (|ΔSMpk|) for Tb55Fe17.5Al27.5, its broader magnetic transition temperature of 110.4 K associated with ∼26% evident structural order yields the maximum relative cooling power (RCP) of 546.04 J kg−1 among three MGs. Moreover, a novel weighted method for evaluating 3d electron number by consideration of the concentration and species of TM elements was adopted to reveal an inverse correlation between the 3d electron number and Tg/Tx, as well as curie temperature (Tc), |ΔSMpk|, and RCP. It is found that with the decrease of the weighted 3d electron number of TM elements, the thermal stability of rare-earth-base MGs is effectively enhanced ascribed to the strong f - d orbital hybridization effect, along with the enhanced 3d - 3d exchange interaction that induces a high Tc. This work would help us more deeply understand the role of TM elements from the perspective of electronic structure, which is crucial for designing the novel MGs with a tunable MCE and GFA applied in various cryogenic refrigeration fields.